BEYOND AREDS2: NEXT-GENERATION NUTRITIONAL SUPPLEMENTS FOR AGE-RELATED MACULAR DEGENERATION - Maja Ćwiek,; Amin Omidi,; Bartosz Krawiec,; Bartosz Zarębski,; Olaf Jadanowski,; Jakub Sójka,; Maksymilian Szombara,; Michał Mokrzyński,; Piotr Szyszka,; Klaudia Malec, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Age-related macular degeneration (AMD) remains the leading cause of irreversible vision loss in older adults worldwide. While the AREDS2 formula has represented the standard of care for nutritional supplementation in intermediate AMD, emerging evidence suggests that newer compounds may offer enhanced protection against disease progression.Methods: This systematic review evaluates literature identified in PubMed, Scopus, and Web of Science up to July 2024. The analysis concentrates on clinical trials, observational research, and mechanistic studies concerning next-generation supplements for AMD, such as astaxanthin, resveratrol, flavonoids, and apocarotenoids.Results: We identified 42 relevant studies demonstrating that novel compounds address limitations of the current AREDS2 formulation through superior antioxidant properties (astaxanthin exhibits 10-100 times greater potency than lutein), enhanced anti-inflammatory effects (resveratrol reduces mtROS by 50%), and improved mitochondrial protection. Apocarotenoids like crocetin and norbixin show enhanced bioavailability and retinal protection compared to traditional carotenoids. Combination approaches targeting multiple AMD pathways simultaneously appear most promising.Conclusion: Current evidence indicates that these novel compounds, particularly when combined with specific carotenoids, may represent a significant advancement beyond the current AREDS2 formulation. Further clinical validation is necessary to establish optimal dosing protocols and long-term safety profiles, but the emerging evidence supports a shift toward personalized, mechanism-based supplementation strategies for AMD management.